CFD simulation of flow control with energy promoters in S-shaped diffuser - Jessam, R.A. (Asian Research Publishing Network, 2017)
This paper presents the computational fluid dynamic (CFD) simulation results for an S-shaped aggressive diffuser. Energy promoters (EPs) were distributed in different locations and configurations along this diffuser to establish its effectiveness in improving flow patterns. The simulated flow field was generated within a normal S-shaped diffuser with a high curvature of 45 °/45 °, and the total length of this diffuse was reduced by 22. CFD simulation was performed on both normal and aggressive diffusers, as well as with and without EPs, through ANSYS-FLUENT commercial software. The renormalized group k -ε model was used to simulate turbulence. The simulation results were validated and were consistent with the findings of previous experimental and numerical studies. Results obtained in the current study indicated that the combination of EPs effectively controls flow distortion in S-shaped aggressive diffusers. Performance parameters, such as the coefficients of static pressure recovery and total pressure loss, suggested that the performance of the five pairs of promoters attached to a specific location at the top and bottom surfaces was optimized; pressure recovery was increased by 47 and total loss coefficient was reduced by 56 in comparison with the case of a normal diffuser. © 2006-2017 Asian Research Publishing Network (ARPN). All rights reserved.